The development in the law of nervous shock / Abdul Haris Abu Bakar - Abu Bakar, Abdul Haris (Faculty of Law, 1984)
The law of nervous shock as an area of tort has gone through tremendous change since the late 19th Century. This area of tort is yet to develop in this country although it is rapidly expanding in other common law countries particularly in England and Australia. The writer feels that there is a need to compile the subject for greater knowledge and understanding and for the benefit of students and lawyers. The purpose of this paper is to trace the development until the existing principle propounded from the very recent case of MC LOUGHLIN V. 0' BRIAN. This paper will deal with the difficulties faced by the courts and will forcast a change in judicial attitude where judges now tend to be more symphatetic towards "genuine" nervous shock victims.